INTERFERENSI KALIMAT BAHASA MANGGARAI TERHADAP BAHASA INDONESIA DALAM PERCAKAPAN MAHASISWA MANGGARAI DI UNIVERSITAS PGRI ADI BUANA SURABAYA - Imelda Mentrana Satria; Eko Cahyo Prawoto (Buana Bastra, 2020)
Interference is a language error caused by the influence of other languages, which is often used so that it affects the use of other languages. This study aims to describe the interferences of Manggarai language sentences in the form of question sentences and command sentences towards Indonesian in Manggarai student conversations at PGRI Adi Buana University, Surabaya This research uses a descriptive qualitative approach that is the explanation in the form of sentences or language. The data from this study are the results of conversations by Manggarai students. The data source of this research is Manggarai students at PGRI Adi Buana University in Surabaya. The techniques of data collection in this study are (1) see competent involvement. (2) record. (3) note it down. The data analysis technique in this study uses descriptive techniques because it strongly supports the research objective of describing or obtaining a clear picture of the form of sentence interference in Manggarai student conversations at PGRI Adi Buana University in Surabaya. The results of the study found in the interference of Manggarai language sentences against Indonesian in Manggarai student conversations at PGRI Adi Buana University Surabaya, in the form of question and command sentence interference. Interference of question and command sentences as found in the structure of Indonesian language is not logical that is influenced by the local language system or mother tongue.